LEGAL PROTECTION FOR DEBTORS ON THE GUARANTEE OF MOTOR VEHICLE OWNERSHIP BOOK (BPKB) IN COOPERATIVE CREDIT LOANS - Indra Tua Manik; Siti br. Ginting (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
The legal position between the debtor and the debtor in the bond agreement, where the borrower has the right to return proof of ownership of the collateral after the loan payment, while the borrower has the right to a higher bond amount, and the billing period in accordance with the guarantor who is entitled to payment plus principal (interest) with the borrower's monthly installments including compensation in the event of late payment. Settlement of disputes related to credit agreements, where the person concerned can arbitrate the agreement in question. Legal observations made by the judge in the decision of Case No. 70 / Pdt.G / 2020 / PN.Mdn, where the judge is of the opinion that the plaintiff has won legally there is no action taken by the Defendant on behalf of Mas Arif Fauzan and verstek. The issuance of this decision is binding on both parties because it has permanent legal force ( incracht ) and has become a new law for the parties. The judge made the decision based on previous legal opinions and the judge's belief that presenting a legitimate and persuasive action is a breach of contract.